(untitled) (Research, Society and Development, 2023)
Objective: This study has the objective correlate sleep disturbances and mood disorders with suicide behavior, showing that the quality of sleep, when altered, interferes negatively in the individual’s daily life, compromising social and labor aspects significantly, leading to a higher incidence of psychiatric disorders, which can incite suicidal behaviors. Methods: This article presents a narrative literature review based on the analysis of scientific articles published from 2009 to 2022 in PubMed on sleep deprivation and suicidal behavior. Results: The results certainly showed that quality and the minimum amount needed of sleep, when altered, interferes negatively in the individual’s daily life, compromising social aspects significantly, leading to a higher incidence of disorders and acute and chronic diseases, such as schizophrenia , depression, anxiety, Alzheimer’s and Parkinson’s,increasing the risk of infectious diseases, cardiovascular diseases, cancer suggesting that the impact of the sleep-wake cycle on anatomy physiology is significant. Conclusion: The study showed that establishing a causal relationship between sleep and mood becomes indispensable to contribute to the development of conventional interventions to promote earlier approaches to sleep and mental health. It was also able to contemplate that sleep disturbance presents itself as a factor, worthy of incorporation into standardized frameworks, for suicide risk assessment and a growing body of research suggests that sleep complaints may be associated with an increased risk of suicidal ideation, suicide attempts and death by suicide, concluding that suicide is largely influenced by changes in the circadian cycle. ‎